Low-latency communication for fast DBMS Using RDMA and shared memory - Fent, Philipp; Van Renen, Alexander; Kipf, Andreas; Leis, Viktor; Neumann, Thomas; Kemper, Alfons (Proceedings - International Conference on Data Engineering, 2020)
While hardware and software improvements greatly accelerated modern database systems' internal operations, the decades-old stream-based Socket API for external communication is still unchanged. We show experimentally, that for modern high-performance systems networking has become a performance bottleneck. Therefore, we argue that the communication stack needs to be redesigned to fully exploit modern hardware - as has already happened to most other database system components.We propose L5, a high-performance communication layer for database systems. L5 rethinks the flow of data in and out of the database system and is based on direct memory access techniques for intra-datacenter (RDMA) and intra-machine communication (Shared Memory). With L5, we provide a building block to accelerate ODBC-like interfaces with a unified and message-based communication framework. Our results show that using interconnects like RDMA (InfiniBand), RoCE (Ethernet), and Shared Memory (IPC), L5 can largely eliminate the network bottleneck for database systems.
CRIS-Team Scopus Importer:2021-04-12